Forgettable in the care of liver cirrhosis: the unseen culprits of progression from bad to worse - Maha Elsabaawy; Omkosoum Alhaddad (Gastroenterology Review)
Patients with liver cirrhosis constitute a critically ill and unique population, and their stability relies on a well-coordinated multidisciplinary team with a carefully structured plan. Overlooking any aspect of this plan can expedite disease progression, leading to severe complications. The lack of disease-specific nutritional guidance, the prevalent sedentary lifestyle among patients, and insufficient screening for hepatocellular carcinoma, oesophageal varices, sarcopaenia, minimal hepatic encephalopathy, and diabetes mellitus, along with fibrosis progression and cirrhosis decompensation, can add further complexities. Additionally, devaluing the impact of obesity in triggering liver cirrhosis can be disadvantageous. Prolonged and inappropriate use of proton pump inhibitors also poses a significant challenge with a wide range of complications. These often-unheeded aspects in the care of liver cirrhosis patients represents the unseen culprits of progression from bad to worse and warrant serious consideration.